Assessment of Accuracy and Naturalness in the Subtitle Translation of Supernatural TV Series - Kevin Johan Halim Saputra; Julia Eka Rini (Institute of Research and Community Outreach - Petra Christian University, 2021)
Fan subtitle or fansub is assumed to be substandard in terms of translation accuracy and naturalness. However, it is not truly known whether fansub translation is really poor in quality or that it can be accurate and natural. This qualitative research analyzes the naturalness and accuracy found in the fansub of an episode of a TV series “Supernatural”, in which the utterances of Dean and Sam Winchester are analyzed using Newmark’s theories on naturalness and accuracy in translation. The translation can be classified into several different categories, which are natural and accurate, unnatural and inaccurate, unnatural but accurate, and could be more natural but accurate. The findings of the research showed that the overall translation cannot be said as completely natural and accurate because it still contains inaccuracies and unnaturalness in its translation, but doesnot significantly change the original messages of the text.Keywords: Translation, Accuracy, Naturalness, Fansub, Supernatural